Electric scooter craniofacial trauma - Faraji, Farhoud (Laryngoscope Investig Otolaryngol, 2020)
OBJECTIVE: The use of standing electronic scooters associated with micromobility applications (e‐scooters) has risen nationally. The aim of this study was to obtain a detailed view of soft tissue and bony craniofacial injury associated with e‐scooter‐related trauma. METHODS: Single‐institution retrospective case series of patients presenting to a level 1 trauma center emergency department or trauma unit with documented e‐scooter‐related craniofacial injury. RESULTS: Of 203 included patients, 188 (92.6%) patients sustained craniofacial injury. One hundred thirty‐one (64.5%) had exclusively soft tissue injury, 3 (1.5%) exclusively bony injury, 51 (25.1%) both soft and bony injuries, and twenty‐five (12.3%) patients sustained dental injury. Aesthetic units most frequently sustaining acute soft tissue injury were the forehead (n = 106, 34.6%), scalp (n = 36, 11.8%), chin (n = 34, 11.1%), upper lip (n = 32, 10.5%), and cheek (n = 31, 10.1%). Aesthetic subunits most often sustaining acute soft tissue injury included the brow (42, 13.7%), central forehead (39, 12.7%), lateral forehead (n = 25, 8.2%), and upper lip vermillion (n = 23, 7.5%). Craniofacial osseous fracture most often occurred in the orbit (n = 42, 24.6%) and maxilla (n = 40, 23.4%). Individual osseous segments most frequently sustaining acute fracture included the anterior maxillary sinus wall (n = 22, 12.9%), nasal bone (n = 20, 11.7%), lateral orbital wall (n = 16, 9.4%), orbital floor (n = 15, 8.8%), and zygomatic bone (13, 7.6%). CONCLUSIONS: Our analysis demonstrates that most patients presenting to our center with craniofacial trauma sustained acute bony fracture, most often to the midface. Our data of common injuries associated with e‐scooter trauma could inform implementation in the form of facial safety equipment or safety skills training for e‐scooter riders. LEVEL OF EVIDENCE: 4